GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 637624174 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 637624174 records from 13714 constituent datasets: 10974 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 37524 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 286 records from Estudio de la distribución geográfica de Peromyscus ochraventer y análisis de su variabilidad cromosómica. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 57 records from T-RFLP Bacteria 2008 RNA ProFIL. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 1433 records from Naturalis Biodiversity Center (NL) - Crustacea. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 8910 records from El género Bursera en México. Parte II. 83 records from A taxonomic revision of the genus Diplonevra Lioy (Diptera: Phoridae) from China. 14563 records from Base de datos de colecciones de maíces nativos, teocintles y Tripsacum de México. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 6 records from Galeus corriganae sp. nov., a new species of deepwater catshark (Carcharhiniformes: Pentanchidae) from Papua New Guinea. 59335 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 14120 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 1348 records from Inventory of Wari maro forest (Benin). 10532 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 4 records from A comprehensive checklist of earthworm species and subspecies from Vietnam (Annelida: Clitellata: Oligochaeta: Almidae, Eudrilidae, Glossoscolecidae, Lumbricidae, Megascolecidae, Moniligastridae, Ocnerodrilidae, Octochaetidae). 2 records from Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae). 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 378 records from Tsetse flies of East Africa update. 31879 records from Mollusca of Costa Rica (INBio). 8780 records from Artròpodes d'Andorra. 2 records from A new legskate, Sinobatis andamanensis (Rajiformes: Anacanthobatidae), from the Andaman Sea (northeastern Indian Ocean). 220 records from Phthiraptera. 143924 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 30366 records from Oregon State University Herpetological Collection. 6 records from Ortopthera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 18032 records from BLS Rare and Threatened Lichen Records: Wales. 879 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. 57210 records from National Biodiversity Data Bank. Observation records, 1900-2014. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 238546 records from Merseyside BioBank (unverified). 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 233 records from NBMP Woodland Survey. 119 records from Bryozoa of the British Isles. 801 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 3 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 2419 records from Invasión de Pinus spp y la conservación de la diversidad florística en Los Altos de Chiapas, México. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 841 records from Ghent University - Zoology Museum - Vertebrate collection. 10674 records from Specimens of lichen herbarium KPABG. 333 records from Macroarthropods, Isua 2013, Greenland. 51668 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 6 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 713 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2522 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 238 records from Asociación de cactáceas con arbustos en el desierto costero de Topolobampo, Sinaloa. 7 records from Taxonomic review of the genus Zethus Fabricius (Hymenoptera: Vespidae: Eumeninae) from Vietnam with descriptions of four new species. 72 records from The Glyptothorax of Sundaland: a revisionary study (Teleostei: Sisoridae). 206 records from The Diptera Site. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 4092 records from Ross Sea Biodiversity Survey 2004 (BioRoss). 24454 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 2628552 records from International Barcode of Life project (iBOL). 584 records from Florida Keys Reef Visual Census 1998. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 1 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 79 records from Complete list of isolated phyllosphere Methylobacterium strains. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 459992 records from Royal Dutch Angling Association (SVN) - Piscaria. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 2 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 1189 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 1 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 914 records from European Pear Rust (Gymnosporangium sabinae) monitoring. 2604 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 2 records from A new river loach from the main channel of the upper Mekong in Yunnan (Cypriniformes: Nemacheilidae). 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 7 records from Pepper French national collection. 211 records from Nezara viridula records held by the Royal Horticultural Society. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 2213 records from JOI - Herbário Joinvillea. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2187 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 1627 records from University of Calgary Herbarium. 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 3508 records from Entocytheridae (Ostracoda) World Database. 8 records from Siphonaptera. 1 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 7574496 records from OEH Atlas of NSW Wildlife. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 17 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 8151 records from ISE - Herbário ISE. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 2 records from Two new marine flatworms (Polycladida: Pseudocerotidae) from Andaman & Nicobar Islands, India. 1 records from Biology and description of Megaprosternum cleonarovorum sp. nov. (Hymenoptera: Bethylidae) a gregarious larval ectoparasitoid of Cleonaria bicolor Thomson (Coleoptera: Cerambycidae) from India. 5096 records from Atlas de los coleóptera Scarabaeoidea de México. Segunda parte. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 712 records from Aprovechamiento sustentable y conservación de la palma bola (Zamia furfuracea), especie endémica protegida, en la zona de Los Tuxtlas, Veracruz. 99133 records from Landesmuseum Kärnten. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 2 records from The types of Phasmida in the Natural History Museum, London, UK. 787 records from List of Spiders of Prioksko-Terrasnyi Biosphere Reserve. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 1234267 records from A global database for the distributions of crop wild relatives. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 155 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 2 records from Two new species of the genus Phaea Newman, 1840 (Coleoptera: Cerambycidae) from Mexico. 154 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 14319 records from Dry Tortugas Reef Visual Census 2000. 8 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 50348 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 15 records from The Steninae MacLeay, 1825 (Coleoptera: Staphylinidae) of Iran: identification key, checklist of species and a new synonymy. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 1563 records from Mid Ulster Hare Surveys 2012-2015. 1 records from ISM Mammalogy Collection. 3349 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 76343 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 8478 records from International Polar Year and Census of Antarctic Marine Life Ross Sea voyage (TAN0802) biodiversity data. 3674 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 1 records from Palaearctic Hoplitis bees of the subgenera Formicapis and Tkalcua (Megachilidae, Osmiini): biology, taxonomy and key to species. 2038 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 190 records from Herpetofauna laguna El Tinije. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1236 records from Insect Collection (CeStuBio). 22554 records from Computarización de abejas de la colección entomológica de la Frontera Sur. 320 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 26 records from The Mysidae (Crustacea: Peracarida: Mysida) in fresh and oligohaline waters of the Mediterranean. Taxonomy, biogeography, and bioinvasion. 8573 records from HUEM - Herbário da Universidade Estadual de Maringá. 4294 records from Diversidad de hemíptera: heteróptera de Baja California e islas del Golfo de California. 38779 records from Ims fish tag database. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 5525 records from Bryophyte diversity in grassland. 33 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 10500 records from HUFU - Herbarium Uberlandense. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 454 records from Copépodos pelágicos del Pacífico norte mexicano. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 19 records from Revision von Suctobelba trigona (Michael, 1888). 2497 records from InsectScale2008FlowerCover. 29644 records from Phanerogamic Botanical Collections (S). 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 20 records from Truchas Mexicanas. 7034 records from Mollusca collection of National Museum of Nature and Science. 85 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 3 records from MSB Mammal Observations (Arctos). 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 69799 records from African Rodentia. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 119038 records from Jordal. 255334 records from MVZ Herp Collection (Arctos). 22 records from DGGE profiles of selected Gammaproteobacteria from leaf samples. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1500 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 488 records from The ecology of Najas flexilis (Slender naiad). 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 55785 records from PRECIS (KwaZulu-Natal Herbarium). 5709 records from Coleoptera of Piska Forest. 355 records from Herbier G. Garapin (BOUM). 21 records from Kalyptorhynchia (Platyhelminthes: Rhabdocoela) from KwaZulu-Natal (South Africa), with the description of six new species. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 1 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 1 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 3 records from Irene litanga, a new genus and new species in the Polia generic-complex from China (Lepidoptera, Noctuidae, Hadeninae, Hadenini). 56802 records from University of Vienna, Institute for Botany - Herbarium WU. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 18636 records from Ants from the Paraguayan dry Chaco. 5242 records from SANBI: DNA Banking(1987-2011). 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1 records from UConn Mammals. 44 records from Colección e identificación de las especies de Meloidogyne y su distribución en los cultivos más importantes para México. 3255 records from Captura de datos de la Colección de Curculionoidea (Insecta: Coleoptera) de la Universidad Autónoma de Querétaro. 1997 records from Aves de la cuenca media del río Bogotá. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 5133 records from Códigos de barras de la vida en peces y zooplancton de México. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 4137 records from UFG - Herbário da Universidade Federal de Goiás. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1702 records from BioGIS - Bryophytes - HUJ collections. 5202 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 213 records from Colección nacional de palmas de Colombia - JBQ. 50 records from Lindesnes. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 58 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 11 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1150 records from Colección de Entomología - Diptera - Ceratopogonidae. 1599 records from Florida Keys Reef Visual Census 2000. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 4 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 16 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 166 records from Revision and cladistic analysis of the Southeast Asian leaf-dwelling spider genus Calapnita Simon (Araneae, Pholcidae). 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 1515 records from Monitoreo del bentos, nutrientes e isótopos en relación a la salud arrecifal de áreas naturales protegidas del norte de Quintana Roo con mayor vulnerabilidad al cambio de fase arrecifal: Primera Etapa. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 9931 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 11 records from - BID-AF2015-0004-NAC- Collection du Laboratoire d'Entomologie Appliquée de l'université de Lomé. 561 records from Herpetile collection, Natural History Museum, University of Oslo. 2546 records from The atlas of butterflies in Kraków. 212578 records from MVZ Mammal Collection (Arctos). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 1333 records from Inventario computarizado de la colección de parásitos de peces del noroeste de México. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 70222 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 10075 records from Nematoda of Costa Rica (INBio). 189656 records from Australian National Wildlife Collection provider for OZCAM. 909 records from Computarización de la Colección nacional del phylum Porifera Gerardo Green. 3204 records from Faunal Inventory of Morysin Nature Reserve. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 32 records from Sea Ice Nematodes. 12499 records from WhiteSeaPlankton. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 668 records from Freshwater Macrophyte Survey Data. 89874 records from ecoscope_observation_database. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 360 records from Bee species data, InsectScale 2008. 288 records from Fungi of Słowiński National Park, Poland. 22 records from Transferred depository for twenty-seven holotypes of the plant bug and flower bug species recently described from Thailand (Hemiptera: Heteroptera: Miridae and Anthocoridae). 30414 records from BLS Lichen Database: Welsh churchyards. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 353 records from Coastal and marine species. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 10250 records from Census of the flora of Benin. 13186 records from Coleção de Aves do Museu Nacional / UFRJ. 896 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 19 records from A taxonomic monograph of the leaf-litter inhabiting weevil genus Plumolepilius new genus (Coleoptera: Curculionidae: Molytinae: Conotrachelini) from Mexico, Guatemala, and El Salvador. 7104 records from Museu Paraense Emílio Goeldi - Diptera Collection. 1512 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 179937 records from LACM Entomology Collection. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 38659 records from Biota occurrence data from plankton surveys around New Zealand. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 140273 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 7200 records from Bryophyte herbarium, Tromsø Museum. 175 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 80 records from Ecología evolutiva de dos especies invasoras de humedales en la República Mexicana: Arundo donax y Phragmites australis (Poaceae). 24 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 33 records from New records in vascular plants alien to Kyrgyzstan. 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1377 records from Fitoplancton marino frente a Baja California. 1. Bahía de Todos Santos, BC. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 40 records from Museu Paraense Emílio Goeldi - Nematoda Collection. 9887 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 1 records from Two new species of Otiorhynchus Germar, 1822 (Tecutinus Reitter, 1912) from south-western Anatolia (Coleoptera, Curculionidae: Entiminae). 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 56905 records from Online Atlas of vascular plants 2012-2020. 2407 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 6 records from Checklist of the micro- and anophthalmic soil-dwelling weevils of the world (Coleoptera: Curculionidae). 1211 records from CCBER Herpetology Collection. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 46264 records from IAC - Herbário do Instituto Agronômico de Campinas. 4 records from A new species and a new synonymy of the plant bug genus Fulvius from Japan (Hemiptera: Heteroptera: Miridae: Cylapinae). 576 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1 records from Discovery in Japan of the second species of the genus Dolichocentrus Martynov (Trichoptera: Brachycentridae). 60667 records from QLD DERM Coastal Bird Atlas (Trial). 133 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 2662 records from Pink-permanent surveillance of coastal areas: Odonata. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2 records from A new two-pored species of Amphisbaena (Squamata, Amphisbaenidae) from the Brazilian Cerrado, with a key to the two-pored species of Amphisbaena. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 6660 records from Weevils of the Tatra Mts.. 120 records from Variabilidad genética en las poblaciones naturales de la almeja catarina Argopecten ventricosus-circularis (Sowerby II, 1842). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 547188 records from Bee Biology and Systematics Laboratory. 5 records from Order Diptera, family Mydidae. 508 records from Flora leñosa de la reserva La Selva El Ocote. 6 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 38692 records from Bryophyte diversity in forests. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 1 records from A new Indian species of Pardoteleia Kozlov & Lê (Hymenoptera: Scelionidae: Scelioninae) and first description of the male. 4730 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 332 records from Base de datos de las cicadas mexicanas. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 5835 records from UPRM Invertebrate Collection. 2000 records from Herpetofauna de las sierras La Candela, Jerez de García Salinas y El Mastrante. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 10973 records from Evaluación de la situación actual de las poblaciones del pez cachorrito del desierto (Cyprinodon macularius macularius) en la Cuenca del Bajo Río Colorado, Sonora-Baja California, México. 5082 records from Heuschrecken_Raw1. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 92 records from Protozoa Abundance_Microbial Parameters. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 6639 records from Laptev Sea and Nansen Basin Zooplankton, 1993. 6 records from Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil. 13572 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 13833 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 586 records from Portuguese Seaweeds. 120 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 21948 records from HBRG Fungus, Lichen & Lower Plants Dataset. 214 records from Collection of Heteroptera. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 11646 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 6 records from Review of the genus Siemssenius Weise, 1922 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 6506 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México: 3a fase. 176 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 79 records from Hidden diversity in deep-water bandfishes: review of Owstonia with descriptions of twenty-one new species (Teleostei: Cepolidae: Owstoniinae). 2210 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 9761 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 7 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1045 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 86 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 25136 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 114955 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 8594 records from ColRest_Raw1. 3 records from Systematics of a small Gehyra (Squamata: Gekkonidae) from the Einasleigh Uplands, Queensland: description of a new range restricted species. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 4 records from Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 304 records from Bryophytes of Glen Nevis Woods 1987-1988. 3336 records from Bryophytes, fungi and lichens on dead wood. 711 records from Colección Hidrobiológica del Chocó. 536256 records from AntWeb. 70361 records from Actualización de la Colección de Artrópodos con importancia médica (CAIM), Laboratorio de Entomología, InDRE. 1 records from A new species and new records of the genus Neotarsonemoides Kaliszewski, 1984 (Acari: Tarsonemidae) from East Azerbaijan province, Northwestern Iran. 22 records from Retrocitomyia Lopes, 1982 (Diptera: Sarcophagidae): new species, new records, key to males, and an updated catalog. 1288 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 73 records from AMF colonization in Plantago. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5733 records from Small Mammal Research Database. 3 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 73383 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 1 records from Ankerius aenigmaticus, a new genus and new species of aphanodactylid crab symbiotic with polychaetes from the Red Sea coast of Saudi Arabia (Crustacea: Decapoda: Brachyura: Aphanodactylidae). 704 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 812 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 231 records from Shannon Index and species richness for arthropods. 3943 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 176729 records from CAS Entomology (ENT). 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 1 records from Red list project inventory, bryophytes. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 1 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4671 records from Otter in coastal areas - Carcasses. 8 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 400 records from National Taiwan Ocean University. 4 records from Two new species of Melanorivulus (Cyprinodontiformes: Cynolebiidae) from Rio Verde drainage, Upper Rio Paraná basin, Brazil. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 2 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 2192 records from Zoology (Museum of Evolution - Uppsala). 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Lissotes working-group. 925845 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from A new species of Monstrilla Dana, 1849 (Copepoda: Monstrilloida: Monstrillidae) from Korea, including a key to species from the north-west Pacific. 688 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 423 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 829087 records from PlutoF platform observations. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 831 records from Herbarium Senckenbergianum (GLM) - Lichenes. 22452 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 36 records from First Inventory of Sea Anemones (Cnidaria: Actiniaria) of the Mexican Caribbean. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 11574 records from SPSF - Herbário Dom Bento José Pickel. 68 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2484 records from Inventario de la vegetación acuática vascular de cuatro regiones hidrológicas prioritarias del centro de México. 1704 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 8940 records from Actualización y adiciones a la Colección de Poliquetos del Instituto de Ciencias del Mar y Limnología, UNAM. 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 62015 records from MMNS Ichthyology Collection. 499 records from Seasonal dynamics of sub-ice fauna below pack ice in the Arctic (Fram Strait). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6198 records from Plecoptera. 18772 records from RHS lily beetle (Lilioceris lilii) monitoring. 28434 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 4 records from Cave species of the genus Anurida (Collembola: Neanuridae) from Korea, with the description of new species. 361 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 9 records from Description of a new species of the Afrotropical spider genus Afroneutria (Araneae, Ctenidae). 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 3057 records from Florida Keys Reef Visual Census 2010. 12958 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 890905 records from PRECIS. 29 records from Genetic variation of the 30 beech stands across three exploratories. 4457 records from Passalidae y Lucanidae (Coleoptera: Scarabaeoidae) de México. 1157 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 31758 records from CSIRO Ichthyology provider for OZCAM. 54211 records from Cawthron Institute freshwater invertebrate data. 9085 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 158924 records from Herbario Nacional Colombiano (COL). 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 23 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 434 records from Distribución, abundancia y hábitat de la liebre endémica Lepus flavigularis. 337 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 28172 records from Notes from the Mycology Herbarium, Oslo (O). 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1200 records from Monocotyledonous Geophytes of Fergana Valley. 1427 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 59522 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 501117 records from Fishbase. 4 records from A new genus of freshwater crab of the tribe Kingsleyini Bott, 1970 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) with description of a new species from Mato Grosso, Brazil. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 9 records from Opistognathus ensiferus, a new species of jawfish (Opistognathidae) from the Gulf of Mannar, India, with redescription of O. solorensis Bleeker. 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 4 records from Australian freshwater sponges with a new species of Pectispongilla (Porifera: Demospongiae: Spongillida). 91719 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 9823 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 743 records from Inventario de especies de vertebrados para apoyar la creación del Ordenamiento Ecológico y la Reserva de la Biósfera Janos, Chihuahua. 1907 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 1 records from Fiocruz/COLPROT - Coleção de Protozoários. 6425 records from Likona Invertebrates. 5 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 14564 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 3 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 5816 records from Flora del municipio de Culiacán, Sinaloa. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 28822 records from EPA River Biologists data. 190 records from Relative abundance of ostracods in sediment core Sv09. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 170 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 1008 records from UTEP Plants (Arctos). 135 records from Registros biológicos recogidos en el marco del proyecto Census of Marine Life Componente Natural Geography in Shore Areas - NAGISA Santa Marta. 106606 records from Occurrence records of southern African aquatic biodiversity. 8 records from Helfer H. 1936. The fishery grounds near Alexandria. VIII Pantopoda. Notes et memoires No 16. 7265 records from NHM, Heteroptera. 1163 records from Paläontologie Marburg. 1 records from A new species of the genus Rhinoecetes Just, 1983 (Crustacea: Amphipoda: Ischyroceridae) from Japan. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 7275 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 835 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 3 records from First record of the thread-legged assassin bug genus Proguithera from Japan, with description of a new species (Hemiptera: Heteroptera: Reduviidae). 1930 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 196 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 21 records from Hyolithen - SMF. 17618 records from BioGIS - Mammals - INPA database. 139243 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 1 records from The natural history and morphology of two bromeliad associated hispines from Brazil: Acentroptera basilica Thomson, 1856 and A. cf. tessellata Baly, 1958 (Coleoptera: Chrysomelidae: Cassidinae: Sceloenoplini). 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 18 records from Metrocoris Mayr (Insecta: Hemiptera: Gerridae) of India with descriptions of five new species. 35344 records from SPF - Herbário da Universidade de São Paulo. 6 records from Phthinia Winnertz (Diptera: Mycetophilidae): new species and records from the Neotropical and Oriental regions. 1 records from On the mammals collected by Friedrich Sellow in Brazil and Uruguay (1814 – 1831), with special reference to the types and their provenance. 14 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 5 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 28 records from Cerambycidae (Insecta: Coleoptera) of Quixadá, Ceará State, Brazil: new records and new species. 4967 records from SANT Herbarium vascular plants collection. 3 records from Collection Myriapoda - SNSD. 139 records from Genética poblacional y filogeografía de las tortugas marinas golfina (Lepidochelys olivacea) y laúd (Dermochelys coriacea) en el Pacífico mexicano. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 4511 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 4864 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 9349 records from Harriet Irving Botanical Gardens (HIBG). 135 records from Programa Integral de Protección de tortugas marinas. Temporadas 2007 a 2012. 6 records from A mountain of millipedes IV: Species of Prionopetalum Attems, 1909, from the Udzungwa Mountains, Tanzania. With notes on “ P. ” fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae). 89461 records from New Zealand Freshwater Fish Database. 759 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 174560 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 181 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 165822 records from KUBI Mammalogy Collection. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 595086 records from SEFSC CAGES Alabama Fish Length Data with CPUE. 16 records from Projeto Abrace o Boto Cinza. 4432 records from Lepidoptera (Observations). 494 records from Taxonomic revision of Stigmatomma Roger (Hymenoptera: Formicidae) in the Malagasy region. 8087 records from Biological Reference Collections ICM CSIC. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 8446 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 353 records from Colección de Entomología - Arthropoda. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 17985 records from UFP - Herbário UFP - Geraldo Mariz. 29 records from New and poorly known Palaearctic fungus gnats (Diptera, Sciaroidea). 3176 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 57 records from T-RFLP Acidobacteria 2008 RNA ProFIL. 328 records from Insect Collection from New Caledonia. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 1125 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 3 records from Amended diagnosis of the genus Nannodiaptomus (Copepoda, Calanoida), based on redescription of N. phongnhaensis and description of a new species from caves in central Vietnam. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3083 records from Finnish Entomological Database: Heteroptera. 13 records from Perot Museum of Nature and Science. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 1432 records from University of Amsterdam (NL) - Páramo pollen reference collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 61 records from Registros restauración ecológica- Magdalena medio. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 957 records from Evaluación del estado de conservación de las poblaciones de Passerina ciris, P. leclancherii, P. amoena, P. rositae, P. caerulea, Cardinalis cardinalis y C. sinuatus en México: recomendaciones para su conservación y aprovechamiento sustentable. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 32182 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 47 records from Empria and Monsoma in Japan. 25971 records from NPL collections. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 17425 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 592367 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 3 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 226 records from Tejidos colectados en la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 47 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 69793 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2011 records from Local BioBlitz Challenge 2013. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 1260 records from Taxonomía de los pinos del noreste de México. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 8 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 1068928 records from FLORIVON. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 44744 records from Dry Tortugas Reef Visual Census 2014. 132439 records from HBRG Insects Dataset. 3133 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 3044 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 1955 records from VMNH Invertebrate Paleontology. 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 2307 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 17482 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3262 records from MBML-Mamiferos - Coleção de Mamíferos. 3732 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 382 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 17 records from On the genus Elasmopus Costa, 1853 from the Northeastern Coast of Brazil with five new species and new records. 2089 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 2829 records from Macroalgas marinas de la Región de Zihuatanejo, Gro.. 5 records from A new species of Cicadatra Kolenati, 1857 from China, with primary phylogenetic analyses of the tribe Cicadatrini (Hemiptera: Cicadidae). 213 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 220 records from Conocimiento y conservación de las mamilarias endémicas del Valle de Tehuacán-Cuicatlán. 2239002 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1157 records from API_CRSN_Data. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 6139 records from HERBAM - Herbário da Amazônia Meridional. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 23366 records from Herbario Pontificia Universidad Javeriana. 2107 records from MLZ Mammal Collection (Arctos). 21733 records from ICN - Herbário do Instituto de Ciências Naturais. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 13 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 4 records from Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina. 28363 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 4214 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 1 records from The first described male Tube-web Spider for mainland Australia: Ariadna kiwirrkurra sp. nov. (Araneae: Segestriidae). 4027 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 22979 records from IICT Herbário LISC. 51034 records from Karplanter i vernet barskog og edelløvskog. 79951 records from Herbario Universidad de Antioquia (HUA). 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 168 records from Estudio poblacional y conservación del mono araña (Ateles geoffroyi yucatanensis) en la región nororiental Península de Yucatán. 1994 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 1093 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 2 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 8235 records from URM - Herbário Pe. Camille Torrand. 628094 records from Inventario Español de Especies Terrestres (MAGRAMA). 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 51285 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 209509 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 38483 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 652 records from Spider species diversity from wet and dry habitats. 1374 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 103104 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 596 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 16779 records from Árboles de Chiapas: registro georreferenciado de los ejemplares depositados en el herbario de la Academia de Ciencias de California (CAS). 593 records from Collection Crustacea - KAUMM. 2113 records from Flora ficológica de la huasteca potosina. 265 records from 16S rRNA gene (V2-V3 region) based analysis of soil procaryotic community composition, Alb VIPs 2008. 20 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 8 records from Five new feather mites of the subfamily Pterodectinae (Acariformes: Astigmata: Proctophyllodidae) from passerines and hummingbirds (Aves) of Brazil. 44 records from Solanum_baretiae. 999 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 338 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 1059 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 10246 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 1 records from On the Ampedini Gistel, 1848 (Coleoptera: Elateridae) of Central Asia, with a description of a new species of the genus Reitterelater Platia & Cate, 1990. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 1 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 3257 records from fundiv france database. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 414 records from Colección de Reptiles del Instituto Alexander von Humboldt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 8613 records from Malezas introducidas en México. 61980 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 1 records from Herpetology. 3000 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 71593 records from The avian collection at the Natural History Museum, Oslo, Norway. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 2240 records from Fongs d'Andorra. 1244 records from Abundanz_Infloreszenzenschlupf_Subplotebene_2008. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 891 records from National Museum of Marine Biology and Aquarium. 4 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 167 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 151 records from Protozoa abundance and microbial parameters, 2008 and 2009. 8487 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 417374 records from Entomology, Natural History Museum, University of Oslo. 1000 records from Demografía e historia de vida de la lagartija Xenosaurus newmanorum en Xilitla, San Luis Potosí. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 114 records from qPCR Ribosomecontent Explo 2008. 3785506 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 38 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 615 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 52392 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 7 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 231935 records from Lyman Entomological Museum (LEMQ). 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 42 records from Revision of the spider genus Gippsicola Hogg, 1900 (Araneae: Segestriidae). 25053 records from NBMP Roost Count. 945 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 2 records from Two new species of Bungona Harker, 1957 (Ephemeroptera: Baetidae) from Borneo, Indonesia. 25132 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 2279 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 9757 records from Collection of Coleoptera. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 52 records from Isotope tracer experiment: meiofauna counts. 5053399 records from Southern African Bird Atlas Project. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 63 records from (Data S1) Palynology of ODP Site 119-739. 181 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 678 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 1474 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 367 records from published Chenopodium vulvaria observations. 455 records from SIO_FAMIZ. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 7403 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 5701 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 30 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 160 records from New species of the damselfly genus Argia from Mexico, Central America and Ecuador with an emphasis on Costa Rica (Insecta: Odonata: Coenagrionidae). 534 records from Ascomycetes of Russian Fennoscandia. 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 4854 records from Inventario de las especies de hongos microscópicos en el Valle de Zapotitlán, estado de Puebla. 506 records from Inventory of Dogo-Kétou forest (South-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 2 records from Four new species, taxonomic, and nomenclatural notes in Hammatoderus Gemminger & Harold, 1873 (Coleoptera, Cerambycidae, Lamiinae). 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 104 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán. 1 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 28369 records from IMOS - AusCPR: Phytoplankton Abundance. 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 4 records from Ecología y comportamiento de dos carnívoros del Bolsón de Mapimí, Durango. 506 records from Nemátodos acuáticos de vida libre de Quintana Roo. 2 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 1163 records from Detección de reclutas de la dorada Sparus aurata como medida del nivel de establecimiento en la Bahía de La Paz, BCS. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 116639 records from The digitization of plant specimens of NTU. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 71 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 481 records from IPOE_Benthos_Steffens. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 1708862 records from SA Flora (BDBSA). 129451 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 3585 records from Census of medicinal and agroforestry plants of Benin. 495696 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 79407 records from NCSM Fishes Collection. 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 1518 records from Florida Keys Reef Visual Census 1997. 194 records from Colección Herpetológica de la Patagonia. 1359 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 8866 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 55317 records from Local Wildlife Site Surveys Berkshire. 55 records from Galls on Beech Trees in Hainich, 2008. 1423 records from Reptilia notes, NTNU University Museum. 3 records from Review of the genus Sophonia (Hemiptera: Cicadellidae) with three new species from India. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1660 records from Avifauna del Altiplano de San Luis Potosí. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 15 records from Eight new species of MacvIcarIa Gibson and Bray, 1982 (Digenea: Opecoelidae) mainly from endemic temperate marine fishes of Australia. 27192 records from Radiolaria specimens from the Norwegian Sea. 484 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 84 records from Colección de Referencia de Equinodermos del Museo de Ciencias de la Universidad El Bosque. 3 records from On Jungicephus Maa (Hymenoptera: Cephidae) with description of a new species from China. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 1051 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 100 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 63598 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 655 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 5056 records from Ontario BioBlitz Species Records. 72295 records from NINA Vanndata øvrige arter. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 3 records from Unraveling a new lineage of Hydrobiidae genera (Caenogastropoda: Truncatelloidea) from the Ponto-Caspian region. 77522 records from Avifauna de la Reserva de la Mariposa Monarca. 129402 records from AM: Freshwater Invertebrates (1900-2005). 198 records from Tortue Olivâtre. Données publiées dans le cadre du projet JRS Bénin. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 724 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 100 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 62500 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 1400 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 12247 records from ULg_Hexapoda. 2846 records from Coleoptera, NEF. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 1655 records from Florida Keys Reef Visual Census 1995. 11 records from Pollen profile from sediment core AV14_K2-4. 10858 records from Lichen diversity in forests. 6948 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 1 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 4 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 222 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 347 records from Peces, ictioplancton y helmintos parásitos en la Bahía de Chetumal (Santuario del Manatí). 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 74 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 603 records from Estudio monográfico del género Echinopepon Naud. (Cucurbitaceae) en México. 6 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4202 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 34 records from Aschelminth collection of National Museum of Nature and Science. 1 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 378646 records from BioFokus. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 90 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 24912 records from Amphibian Specimens. 153760 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 355 records from Culture Collection of Cryophilic Algae. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 129 records from Estudio florístico, ecológico y etnobotánico, en el área natural protegida "Tenancingo-Malinalco-Zumpahuacan", Estado de México. 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 24 records from Ice Diatoms Arctic Basin 1977, 1980. 2 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 4 records from Description of the first species of Gonadryinus Olmi (Hymenoptera, Dryinidae) from the Afrotropical region. 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 7366 records from Caracterización y monitoreo de la condición arrecifal en cinco áreas naturales protegidas y un área de influencia de Quintana Roo, México: Primera etapa. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 4977 records from Florida Keys Reef Visual Census 2007. 2 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 210 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 8473 records from UAM Fish Collection (Arctos). 10 records from First occurrence of Nemobiinae crickets in the Lesser Antilles (Orthoptera, Grylloidea, Trigonidiidae), with the descriptions of three new species. 38619 records from DMNS Bird Collection (Arctos). 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 78799 records from natagora-earlybirds. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3688 records from Clare Biological Records Centre dataset. 8 records from A new species of Acanthocaudus Smith (Braconidae: Aphidiinae), with a key to species and new host and distribution records for aphidiines associated with Silphium perfoliatum L. (Asterales: Asteraceae). 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 2466 records from TTRS Ornithology. 8583 records from The Fish Collection at the Zoologische Staatssammlung München. 2296 records from Species composition of protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of JRS Biodiversity Foundation project. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 382283 records from University of Florida Vertebrate Paleontology. 582 records from Bioblitz 2013 Copenhagen Denmark. 80907 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 299187 records from Coordinated Waterbird Counts. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 2 records from A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey. 9855 records from Bibliographic records of Angola mammals. 5 records from Revalidation of Platystigma Kennedy, 1920, with a synopsis of the quadratum species group and the description of three new species (Odonata: Pseudostigmatidae). 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 1 records from Spelaeogammarus uai (Bogidielloidea: Artesiidae): a new troglobitic amphipod from Brazil. 12 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 7 records from Description of Eutetrapha weni n. sp. from Guizhou, China (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 36356 records from Dry Tortugas Reef Visual Census 2012. 614 records from Naturalis Biodiversity Center (NL) - Odonata. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 72015 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 2686 records from Análisis de viabilidad para poblaciones de la cactácea amenazada Ariocarpus trigonus. 236 records from GENT Lactarius Deliciosi. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 1422 records from Algas coralinas articuladas (Rhodophyta-corallinales) de México. 201 records from BioAcoustica: Wildlife Sounds Database. 6 records from A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil. 4 records from A new species of Protaetia Burmeister, 1842 from Armenia with taxonomic notes on Cetonia floricola fausti Kraatz, 1891 (Coleoptera: Scarabaeidae: Cetoniinae). 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 3 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 34 records from Sipuncula collection of National Museum of Nature and Science. 588 records from Relative abundance of ostracods in sediment core Lz1120. 1 records from Three new Sisyphus species (Coleoptera: Scarabaeidae: Scarabaeinae) from shaded vegetation in southern Africa. 6566 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 755 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 1832 records from National Earthworm Recording Scheme Records (Great Britain). 25983 records from Monitoring data from the federal state Bavaria (Germany). 6213 records from Museu Paraense Emilio Goeldi Herbarium. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 4 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 7 records from Further studies on south eastern Asian Luciolinae: 1. Sclerotia Ballantyne, a new genus of fireflies with back swimming larvae 2. Triangulara Pimpasalee, a new genus from Thailand (Coleoptera: Lampyridae). 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 567 records from Collection of Hymenoptera. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 1972 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 393 records from Danish Lacewings (Neuroptera). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 10150 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 101 records from Macroalgas marinas de Baja California Sur Parte I: Bahía de la Paz y Bahía de la Ventana. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 175 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 747 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 11742 records from Inventario florístico de la familia Boraginaceae en México. Fase II. 2 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 20 records from Taxonomic review of the genus Atlantodesmus Hoffman, 2000 (Polydesmida: Chelodesmidae). 7311 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 3040 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 1349 records from MODIRISK:RBINS Diptera: Culicidae Collection. 34 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 543 records from OUPR - Herbário "Professor José Badini". 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 45 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 22105 records from Global compendium of Aedes albopictus occurrence. 1 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 2 records from A new species of Nemipterus (Perciformes: Nemipteridae) and first record of N. nematophorus (Bleeker) from Taiwan. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 43 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 2 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 179061 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 907 records from Base de datos de la familia Fagaceae en el estado de Hidalgo. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 1620 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 14 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 146 records from Megophthalmidia_of_North_America. 14412 records from Records from the RHS insect reference collection. 1 records from Revision of Ogdoecosta Spaeth 1909 with description of Ogdoecosta paraflavomaculata López-Pérez, sp. nov. (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini). 111 records from Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 25674 records from Diatomeas (Bacillariophyceae) y Dinoflageladas (Dinophyceae) planctónicas más frecuentes en la región sur del Golfo de México. 17062 records from Coastal Saltmarsh Monitoring. 58 records from Mamíferos laguna El Tinije. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3372 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 188215 records from NINA insect database. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 13884 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 3591 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 10 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 28338 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 6126 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. 10. Amphipoda Benthonica. Notes and memoirs no 11. 565 records from Ectomycorrhiza species on all VIP´s April 2008. 1 records from Études myrmécologiques en 1886.. 3712 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 2 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 7402 records from Helgeland Museum, Lepidoptera. 873 records from Kartlegging av spredning av fremmede bartrær. 5097 records from HAMAB - Herbário Amapaense. 1420 records from Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 21647 records from National River Water Quality Network Database (Macro-invertebrates). 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 10116 records from CUMV Mammal Collection (Arctos). 55 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 820426 records from Fauna Atlas N.T.. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 41 records from CIM Specimens. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 5 records from New species and new synonyms in European Platypalpus (Diptera: Hybotidae). 17 records from Resolving the status of Pyriporoides and Daisyella (Bryozoa: Cheilostomata), with the systematics of some additional taxa of Calloporoidea having an ooecial heterozooid. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 1303 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 47107 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 1 records from Notes on Cataglyphis Foerster, 1850 of the bicolor species-group in Israel, with description of a new species (Hymenoptera: Formicidae). 13442 records from CUMV Fish Collection (Arctos). 2195 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 10 records from A taxonomic revision of the kalshoveni species-group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae), with descriptions of six new species from Indonesia and Papua New Guinea. 260 records from SuLaMa reptile survey II 2012. 58 records from LISU Herbario Angola. 2642 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 3953 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 3 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 864 records from Rhodolith Beds in Northern New Zealand: Characterisation of Associated Biodiversity. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 54708 records from Field Museum of Natural History (Zoology) Bird Collection. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 1839 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 350615 records from Plantae of Costa Rica (INBio). 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 12250 records from La Colección de Poliquetos (Annelida: Polychaeta) de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 9 records from A new species of Euricrium Enderlein from southern Brazil, new records for E. varians (Lane), a new combination, and a key for the Neotropical species of the genus. 4851 records from Fauna carcinológica de México. Crustáceos estomatópodos y decápodos del Golfo de México. Río Bravo, Tamaulipas a Cabo Catoche, Q.Roo. 28860 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 24977 records from Mycology herbarium, Tromsø Museum. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 115264 records from UAM Mammal Collection (Arctos). 8483 records from IZIKO: Marine Invertebrate Collection (1900-2011). 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 7 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 27 records from HSU Wildlife Eggs and Nests. 2385 records from MATRIX project, Mabira in Uganda. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 24 records from New species of Macunahyphes Dias, Salles & Molineri (Ephemeroptera: Leptohyphidae), with taxonomic notes. 620 records from Digitalización de la colección FITO-UBIPRO, de las enfermedades y sus agentes causales, de los cultivos agrícolas de la región centro de México. 250 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco. 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 77 records from Inhaltsstoffe_Blattmischproben_2008. 325 records from KU E16 Slæn - Tvinno. 158 records from Biodiversidad del Phyllum Mollusca asociada a las plataformas de explotación de gas natural (Campo Chuchupa: La Guajira, Colombia). 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 2 records from Counts of benthos communities in Kongsfjorden in 2009. 4 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 2 records from CCBER Mammalogy Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 136 records from Plants galls. 2 records from Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini. 49196213 records from Artdata. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 36 records from Propuesta de categorías de riesgo para la ictiofauna dulceacuícola de Oaxaca. 310 records from Lepidoptera systematic collection, NTNU University Museum. 108261 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 454 records from Collection des Mollusques (BOUM). 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 345941 records from Reef Life Survey: Global reef fish dataset. 7 records from Two new paratanaid Tanaidacea (Crustacea: Malacostraca: Peracarida) from the Hawaiian Islands, with illustrated taxonomic keys. 12 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 858 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 7348 records from Herbier du Bénin. 3 records from MfN - Micropaleontology. 14 records from Clasificación de tres especies endémicas de Mammillaria dentro del PROY-NOM-ECOL-059-2000. 11746 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 9088 records from Flora of Słowiński National Park, Poland. 690 records from Odonata collection, NTNU University Museum. 1 records from Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. 1280 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 1960 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 747326 records from Museum Victoria provider for OZCAM. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 1335 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 1742 records from Eggs Specimen. 35832 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 27231 records from Butterflies of Ireland. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 5837 records from CRCM Vertebrate Collection. 3 records from Anopheles prachongae, a new species of the Gigas Complex of subgenus Anopheles (Diptera: Culicidae) in Thailand, contrasted with known forms of the complex. 1463 records from Vertebrados terrestres de San Juan de Camarones, Durango. 216 records from VIP_data_topsoil_jointsampling_microbiolgroups_2008_Heiko_Nacke. 6 records from New genus of diminutive microhylid frogs from Papua New Guinea. 3 records from Diatom abundance of Hole 38-338, Part 2. 137 records from SNH Invertebrate Site Condition Monitoring 2013/14: Alvie SSSI. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 7416 records from The atlas of breeding birds in Małopolska. 461 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 4 records from New taxa and notes on some Landrevinae (Orthoptera: Gryllidae) from Malay Peninsula. 29 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 5 records from A taxonomic review of Korean Liogluta Thomson (Coleoptera, Staphylinidae, Aleocharinae) with descriptions of three new species. 14332 records from Cowan Tetrapod Collection - Mammals. 2911 records from Change in aboveground biomass carbon stock following the establishment of exclosures on degraded lands in Tigray, Ethiopia. 788 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 341 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 14498 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 19973 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 1530 records from Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1292 records from Census of tapia forest plant species in central highland of Madagascar. 1750 records from Flora of tanzania. 7 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 381 records from Priority effects of early successional insects influence late successional fungi in dead wood. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 805 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 12720 records from MBM - Herbário do Museu Botânico Municipal. 314 records from Peces laguna El Tinije. 666 records from Vascular plants from a study of primary producer traits across an altitudinal gradient in alpine Finse. 1905 records from BioGIS - Reptiles - INPA database. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 612 records from INRA-Versailles Arabidopsis natural variants. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 30 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 12184 records from Diversidad de abejas (Hymenoptera: Apoidea) de la Reserva de la Biosfera El Triunfo, Chiapas. 6698 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 2282 records from Ohio University Invertebrate Paleontology Collection. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 13793 records from Flora de las playas y dunas costeras de México. 3 records from Odontotrypes (Odontotrupes) tawangensis new species (Coleoptera: Geotrupidae) from Arunachal Pradesh, India. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2706 records from Alien macro-invertebrates in Flanders, Belgium. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 72 records from The "Martian" flora: new collections of vascular plants, lichens, fungi, algae, and cyanobacteria from the Mars Desert Research Station, Utah. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 27 records from Coleção de Nemertea do Museu Nacional - UFRJ. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 39 records from International Collection of Microorganisms from Plants (ICMP). 2243 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 20 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 32 records from Ice Zooplankton Beaufort Sea. 3197 records from Harvestmen of French Guiana. 2312 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 100757 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 234829 records from Waterbird census in Spain. 41758 records from USGS South Florida Fish and Invertebrate Assessment Network Fish. 10895 records from Stabbetorp - Floristiske registreringer 2016. 2810 records from Helgeland Museum, Araneae. 6438 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 8600 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 5 records from New species of Curculionichthys (Siluriformes: Loricariidae) from the eastern Guiana Shield. 1419 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 82 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 4 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 4972 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 3140 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 2136 records from Herbario Museo de La Salle Bogotá (MLS). 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 15306 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 3400 records from Lista florística de la Costa Grande del estado de Guerrero. 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 625 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 10 records from Five new species and a new country record in American Cerambycidae (Coleoptera). 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 1 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 20664 records from Arctic Species Trend Index (ASTI) : Terrestrial. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 3275840 records from Insecta of Costa Rica (INBio). 17 records from Sarcinoid green algae (Chlorophyta) of Algal Collection of Soil Science Institute (ACSSI). 61614 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 15 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 10584 records from Danish Plant Bugs (Miridae). 1298 records from Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 29114 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 1 records from Recharacterization of Rhinophis dorsimaculatus Deraniyagala, 1941 (Serpentes: Uropeltidae), including description of new material. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 16904 records from Mollusca Collection of the Museu Nacional/UFRJ. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2900 records from Bases para el monitoreo de dos especies de carnívoros medianos en la Reserva de la Biosfera de Mapimí, Durango. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 1 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 4422 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 1 records from Early-diverging bumblebees from across the roof of the world: the high-mountain subgenus Mendacibombus revised from species’ gene coalescents and morphology (Hymenoptera, Apidae). 18703 records from Endemic plants of the Congo basin. 1 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 2 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 93 records from Distribución actual, estatus poblacional y evaluación del estatus de protección del pavo ocelado (Agriocharis ocellata). 353 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 117 records from Various insect orders, NEF. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 22680 records from Arctic Species Trend Index (ASTI) : Marine. 810 records from Chrysomelidae of the Carpathians. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 1430 records from Collection botanique Jaubert et Saul (BOUM). 27975 records from Inventaire National du Patrimoine Naturel : Loup en France. 934 records from GenLink - Collected plant samples on grassland EPs. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1728 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 3 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 880841 records from SA Fauna (BDBSA). 3 records from A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 3284 records from Algae (S). 20 records from Descriptions of larvae of four species of Hydropsyche (Hydropsychidae: Trichoptera) from Thailand. 1652 records from Depletion fishing in the rivers Grote Nete and Kleine Nete in Flanders, Belgium. 1809 records from BenthosChukchiFN762_1976_Falk5. 26017 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 2 records from First record of order Embioptera (Insecta) for the State of Tocantins, Brazil, with description of a new species of Clothoda Enderlein. 1 records from First report of some known Trichodinella epizootica Šramek-Hušek, 1953, and Tripartiella Lom, 1959 from the cultured Oranda Gold Fish (Carassius auratus auratus) in India. 1182 records from Registros faunísticos de invertebrados marinos en el SE del Golfo de California. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 54 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 3276 records from Biología poblacional de Isostichopus fuscus (Ludwig, 1875) (Echinodermata: Holothuroidea) en el sur del Golfo de California. 118 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 2437 records from Fungus herbarium, UiB. 678 records from NCC Berkshire Chalk Grassland Survey 1985. 9157 records from BMSM Bailey-Matthews National Shell Museum. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 71 records from HSU Wildlife Mammals. 127937 records from OHN. 411 records from SuLaMa reptile survey I 2012. 5992 records from Algas marinas bentónicas de la Península de Yucatán y uso potencial de especies selectas. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 22614 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 161917 records from Field Museum of Natural History (Zoology) Mammal Collection. 25 records from Cerdos asilvestrados (Sus scrofa) en la Reserva de la Biosfera Sierra La Laguna: Evaluación e impacto sobre la biodiversidad. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 21672 records from TPWD HARC Texas Coastal Fisheries, Corpus Christi Bay Gill Net. 13 records from Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 431 records from Upper Silesian Museum, Insect Collection. 2 records from Ichthyologie ZMK. 71220 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 199 records from MVZ Hildebrand Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 2 records from The Dixa inextricata Dyar & Shannon (Diptera: Dixidae) species group, with two new cryptic species from the eastern Nearctic Region. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 51 records from Packer Collection / Xenochilicola bees, Chile. 1 records from Ornithologie ZMK. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 50731 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 3 records from Revision of the non-Afrotropical species of Trigastrotheca Cameron (Hymenoptera: Braconidae: Braconinae) with descriptions of four new species. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 506 records from Migración, movimiento y distribución estacional del cachalote en el Golfo de California. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 281 records from Myriapoda of Costa Rica (INBio). 531 records from Expedición Providencia I - INVEMAR. 163 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 185711 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 633712 records from Données ONF Faune-Flore-Fonge. 2 records from Vermes ZMK. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3 records from Revision of the Taiwanese species of the genus Leptophion Cameron, 1901 (Hymenoptera: Ichneumonidae: Ophioninae), with a discussion of their phenology and distribution. 898 records from kyklades. 1 records from Reptilia ZMK. 137 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 7 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 27 records from Root Length and Mass VIP 2008 Rillig. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 843 records from FCAB - Herbário Friburguense. 284 records from Crustacea ZMK. 27061 records from Bird Monitoring Data. 1 records from REDESCRIPTION OF TETRAMORIUM ATLANTE CAGNIANT, 1970, NEW STATUS (HYMENOPTERA: FORMICIDAE: MYRMICINAE). 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 31962 records from Herbier de Nouvelle-Calédonie. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 1 records from Pantopoda SMF. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 6 records from Malakologie ZMK. 2179 records from Base de datos y colección de anfípodos (Hyperiidea:Crustacea) de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 6 records from ZUEC-PLA - Coleção de Platyhelmintes do Museu de Zoologia da UNICAMP. 11 records from Catalogue of the family Ologamasidae Ryke (Acari: Mesostigmata). 2 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 72596 records from CAS Invertebrate Zoology (IZ). 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 6761 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 27 records from Tortugas marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 2 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 17 records from Abyssal fauna of the UK-1 polymetallic nodule exploration area, Clarion-Clipperton Zone, central Pacific Ocean: Cnidaria. 10 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 4240 records from Crustacea collection of National Museum of Nature and Science. 2 records from Echinodermata ZMK. 90 records from Relascope sum of Sitka spruce Picea sitchensis in Fusa and Tysnes. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1111 records from La ballena jorobada, Megaptera novaeangliae, en la Península de Baja California Sur, México. 45697 records from Archives of the Arctic Seas Zooplankton. 1744 records from Status, ecología y conservación de loros Amazona en el Noreste de México. 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 474 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 3 records from A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) from Espírito Santo State, southeastern Brazil and comments on additional species. 48479 records from IMOS - AusCPR: Zooplankton Abundance. 2 records from Endogean and cavernicolous beetles of the Balkans. XVI. A new, anophthalmous species of Neuraphes Thomson, 1859 (Coleoptera: Staphylinidae: Scydmaeninae) from Albania. 965 records from Freshwater plants of Cameroon. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 418564 records from BLS Lichen Database: English churchyards. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 7244 records from MBML-Aves - Coleção de Aves MBML. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 38 records from Harant H. 1939. Les fonds de peche pres d'Alexandrie. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28. Institut fouad 1er d' Hydrobiologie et de peche, Egypt. 287 records from The Sea Ice Fauna of Frobisher Bay, Arctic Canada 1981 and 1982. 16 records from The genus Leucophenga (Diptera, Drosophilidae), part VI: the argentata species group from the East Asia, with morphological and molecular evidence. 60 records from Shrews of Poland. 937 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 490 records from flower availability 2007 Schwäbische Alb. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 12014 records from Tallinn Botanic Garden. 6909 records from Primera fase de actualización de la Colección de Siphonaptera Alfredo Barrera del Museo de Zoología Alfonso Herrera. 2 records from Indopamphantus makutaensis, a new genus and species, and Indopamphantini, a new tribe of Pamphantinae (Hemiptera: Heteroptera: Geocoridae), as the first representative of the subfamily from the Oriental Region. 1 records from Redescription of two European species of Acerentomidae (Protura) belonging to the Italian fauna. 2030 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 200 records from Zoological collection of the National Museum. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 36 records from A revision of the genus Andesipolis (Hymenoptera: Braconidae: Mesostoinae) and redefinition of the subfamily Mesostoinae. 3620 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2864 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 102 records from A Lichen Survey of the Ben Nevis Plateau. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 278 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 2070 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 1523 records from Colección de Zoología Invertebrados - Otros invertebrados. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 619 records from UCM Bird Eggs/Nests Collection (Arctos). 8395 records from Herbarium areqvipense (HUSA). 450 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo en Nuevo León. 119 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 749207 records from Historical Bird Atlas. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 682 records from Megabenthos-Epibenthos Greenland. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 76209 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 4 records from Culture Collection of Algae. 4516 records from CHAS Mammalogy Collection (Arctos). 27 records from synthese_Protistdiversity_KG. 13 records from Taxonomy and immature stages of the Platystomatidae (Diptera: Tephritoidea) of Israel. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 20380 records from UAM Bird Collection (Arctos). 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 688 records from Algae, Norwegian College of Fishery Science. 15866 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1014 records from RHS Hemerocallis midge survey. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 969979 records from Norwegian Biodiversity Information Centre - Other datasets. 94 records from Vascular Plants and Bryophytes of Glen Sligachan. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 144 records from Annelida collection of National Museum of Nature and Science. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 90 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 6131 records from Evaluation de la dynamique des espèces envahissantes (Pistia stratioides et Eichhornia crassipes) et de la flore aquatique au Bénin en association avec ces espèces envahissantes. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 240 records from MPM Herpetology. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 57 records from T-RFLP Acidobacteria 2008 DNA ProFIL. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 3635 records from ZUEC-BIV - Coleção de Bivalvia do Museu de Zoologia da UNICAMP. 2285 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 2 records from Two New Variegated Snailfishes of the Genus Careproctus (Teleostei: Scorpaeniformes: Liparidae) from the Aleutian Islands, Alaska. 574 records from Invasive plant species recorded in protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones of Benin. Data mobilized in the framework of BID Regional project BID-AF2015-0066-REG and funded by EU. 97 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 264 records from Agaricomycotina species reveald by ITS / LSU sequencing. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 296 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 852 records from flower availability 2008 Hainich. 59 records from CCBER Ornithology Collection. 1320 records from Sistematización de la Colección de Algas Marinas del Centro Interdisciplinario de Ciencias Marinas CICIMAR-IPN. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 7 records from (Table 4) New palynological record of sediments from Odderade. 63692 records from La familia Asteraceae en México. Fase VI. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 1151 records from arim. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 2232 records from Computarización de Pterópodos (Thecosomata: Gastropoda) del Caribe de México y Belice. 2 records from A new species of the genus Bothrioplana (Platyhelminthes: Bothrioplanida: Bothrioplanidae) and a new species of the genus Pentacoelum (Tricladida: Bdellouridae) from southern China. 4440 records from Invertebrate collection of University of Oulu Zoological Museum. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 12 records from Naturalis Biodiversity Center (NL) - Mammalia. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 686 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 3313 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 7551382 records from BirdLife Australia, Birdata. 642167 records from Museum of Comparative Zoology, Harvard University. 431 records from BRFC Black Rock Forest Consortium Herbarium. 9192 records from Herbarium of the Université Libre de Bruxelles. 63 records from Marine gastropod distribution from patagonian shallow waters. 7455 records from Actualización de la colección poliquetológica de la Universidad Autónoma de Nuevo León. 1025 records from tef-database. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 15 records from Tardigrada collection of National Museum of Nature and Science. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 118 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 291693 records from SEAPOP NINA. 10502 records from Naturalis Biodiversity Center (NL) - Cnidaria. 5 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 7 records from Discovery of the genus Claraeola Aczél in Iran with the description of two new species (Diptera: Pipunculidae). 4918868 records from Australia's Virtual Herbarium. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1657161 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 16998 records from Modern foraminifera in the New Zealand EEZ. 13315 records from Collection of various insect orders, Natural History Museum, University of Oslo. 36093 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 431 records from Plantas Bosque Seco Chicamocha. 47 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 9948 records from Bees of Canada / Gschwendtner property collection. 450 records from Species Records for John Muir Trust Properties 2007-2009. 3 records from Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data. 697 records from Herbier de Strasbourg. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 544 records from Interacciones en el dosel de la selva húmeda tropical e implementación de un sistema de estudio en este ambiente. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 56431 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 3 records from The cladorhizid fauna (Porifera, Poecilosclerida) of the Caribbean and adjacent waters. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 1133 records from Wood-inhabiting corticioid basidiomycetes in Norway. 3993 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 51638 records from Vascular Plant Herbarium, UiB. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 113 records from Base de datos de Rana catesbeiana.. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 48 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1 records from Applying n-dimensional hypervolumes for species delimitation: unexpected molecular, morphological, and ecological diversity in the Leaf-Toed Gecko Phyllodactylus reissii Peters, 1862 (Squamata: Phyllodactylidae) from northern Peru. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 17 records from Hazel Dormouse in Ireland. 37 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 5924 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 24187 records from NBMP Hibernation Survey. 8124 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 35266 records from Kathryn Kalmbach Herbarium. 3375 records from NMMNH Mammal. 164581 records from Ichthyology Collection - Royal Ontario Museum. 2 records from Ice Amphipods Canada Basin. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 1571 records from Banco de Germoplasma del Jardín Botánico Atlántico. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 715 records from Ictiofauna Lermense. 1294 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 118931 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 4224 records from Actualización de la colección ictiológica de Ecosur-Chetumal. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 1 records from A description of two new species of the genus Erenna (Siphonophora: Physonectae: Erennidae), with notes on recently collected specimens of other Erenna species. 23 records from Redescription of Proformica nasuta (Nylander, 1856) (Hymenoptera, Formicidae) using an integrative approach. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 135609 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 65 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 245 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 21868 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 163 records from Entomofauna laguna El Tinije. 259723 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 6004 records from Colección Limnológica Universidad de Antioquia. 66042 records from CAS Ornithology (ORN). 463 records from Nemátodos acuáticos de vida libre de la cuenca de la Laguna de Términos, Campeche. 3 records from Three new species of tribe Odynerini (Hymenoptera, Vespidae, Eumeninae) from the Neotropical Region. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 561 records from Líquens d'Andorra. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 954 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 74 records from SuLaMa reptile monitoring. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 2288 records from Colección del Banco de Germoplasma de la Universitat de València. 4817324 records from Bird Ringing Centre in Sweden (NRM). 5311 records from Natural History Museum Maastricht (NL) - Herbarium. 9 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 164 records from Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 274304272 records from EOD - eBird Observation Dataset. 1380439 records from Consortium of California Herbaria. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 1 records from The first Turcolana Argano & Pesce, 1980 (Isopoda: Cirolanidae) from the Greek mainland. 1 records from Description of a new species of Priolepis (Perciformes: Gobiidae) from the Red Sea, a new record of Priolepis compita, and a distributional range extension of Trimma fishelsoni. 258 records from Cnidarios del proyecto Macrofauna Corpoguajira. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 2 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 64 records from Mamíferos, aves y peces de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 169 records from The Pteridaceae family diversity in Togo. 3048 records from Distribución, estructura poblacional y utilización del saguaro (Carnegiea gigantea (Engelm.) Britt. & Rose) en México. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 56436 records from Tasmanian Museum and Art Gallery provider for OZCAM. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 49637 records from Monitoring data from the federal state Hesse (Germany). 8014 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 5 records from Revision of the Malagasy species of Homalium sect. Eumyriantheia Warb. (Salicaceae). 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 1383808 records from iNaturalist Research-grade Observations. 311 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 151 records from SNH Invertebrate Site Condition Monitoring 2013/14: Lismore Lochs SSSI. 1 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 16246 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa). 20146 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 5506 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 9741 records from Finnish Entomological Database: Hymenoptera. 163 records from Barcode de Bambúes nativos de México. 46480 records from Insects, Outer Hebrides. 7470 records from National Taiwan University. 62 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 19 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 1 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 790 records from UCBG TAPIR Provider. 25412 records from NCSM Mollusks Collection. 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 946 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 166 records from Simpson´s diversity of Coleoptera and Heteroptera. 5115 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 2262 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3669 records from ARKO strandeng. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 7 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 1589 records from Global caridean shrimp fauna. 3546 records from Dorset SW Pilot species dataset. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 266922 records from Seasearch Marine Surveys in England. 4 records from A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 156129 records from CONN. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 914 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 491 records from Coleccion de Entomología del Instituto de Ciencias Naturales (ICN-MHN-En). 4776 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 34 records from National System of Protected Areas in Poland - Fungi. 1 records from A new shallow water species of Artemisina Vosmaer, 1885 (Microcionidae, Demospongiae; Porifera) from Northeastern Brazil. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 614338 records from Aranzadi Ringing Scheme (bird ring-recovery data). 1073 records from Bryopyhtes in forest indices and traits. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 1077 records from BioGIS - Fish - HUJ collections. 3738 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 1967 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 46 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from A new species and a new record of the spider genus Nesticus (Araneae, Nesticidae) from southern Brazil. 56 records from UCM Vertebrate Observations Collection (Arctos). 22541 records from H.A. Stephens Herbarium. 1 records from A new ant genus from the southwestern United States.. 3 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from Two new species of Indonemoura (Plecoptera: Nemouridae) from Yunnan Province of southwestern China. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 3214 records from Upper Silesian Museum, Bird Observations. 9651 records from CSIRO, fish surveys by the Soela, 1980s. 8407 records from NYSM Birds. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 23 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from Review of the Eriococcidae (Hemiptera: Coccomorpha) infesting Fabaceae in Argentina, with descriptions of three new species of Acanthococcus Signoret. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 40381 records from Recent Invertebrates Specimens. 9672 records from Actualización de la base de datos de la Colección de mamíferos del Museo de Zoología 'Alfonso L. Herrera'. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 13720 records from Hemipteran specimens of Iwate Prefectural Museum. 57 records from On the Nazeris fauna of Zhejiang, China (Coleoptera, Staphylinidae, Paederinae). 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 180 records from Ecología poblacional de Abies hickelii en el Pico de Orizaba, Veracruz. 6 records from Catalogue of the Teratomyzidae (Diptera, Opomyzoidea) of the World. 26 records from Taxonomic revision and phylogeny of the ant genus Prenolepis (Hymenoptera: Formicidae). 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 43566 records from Merseyside BioBank Active Naturalists (unverified). 4 records from A revision of the species of Evaza Walker described by J. C. H. de Meijere (Diptera, Stratiomyidae, Pachygastrinae). 745 records from El género Festuca (Poaceae: Pooideae) en México. 50000 records from observe_tuna_bycatch_ecoscope. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 4403 records from UFRN-Fungos - Herbário UFRN - Fungos. 71 records from Spiders of French Guiana. 1 records from Distribution of haploniscids (Isopoda, Asellota, Haploniscidae) in Icelandic waters, with description of Haploniscus astraphes n. sp. from the Iceland basin and the Southeast Atlantic Ocean. 12 records from Taxonomy of the Mexican species of Thyreocephalus Guérin-Méneville (Coleoptera: Staphylinidae, Xantholinini). 2877 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 2 records from Eggplant French national collection. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 17344 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 31 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 9 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 4684 records from Coleção de Polychaeta do Museu Nacional. 1 records from Description of a new species of Thevenetimyia (Diptera: Bombyliidae) from Madagascar, with a revised checklist of Madagascan bee fly fauna. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 65 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 7473 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 19 records from Flora of Japan Specimen Database. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 18 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 10 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 8941 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forèts sacrées des départements de l'Ouémé-Plateau et le Collines. Données mobilisées dans le cadre du projet JRS Bénin. 870 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 422 records from Estructura genética y conservación de la tortuga negra Chelonia agassizi en el Pacífico mexicano. 6309 records from University of Lethbridge Herbarium (LEA). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 14 records from Two new species and new records of the genus Paraopisthosyllis Hartmann-Schröder, 1991 (Annelida: Syllidae) from northeastern Brazil and Philippine Islands. 3602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 554 records from SNH Invertebrate Site Condition Monitoring 2013/14: Abernethy Forest SSSI. 103322 records from Invertebrates Collection of the Swedish Museum of Natural History. 442 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 9640 records from KUBI Ichthyology Tissue Collection. 21 records from A revision of the genus Eutetrapha Bates (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 1894 records from Fungi Collection. 27534 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 181 records from Alien Species in Poland - Animals. 82287 records from AM: Terrestrial Insect Collections (1896-2000). 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 66346 records from Global Lacustrine Diatoms. 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 39385 records from SAEON: Historical Research Survey Database (1897-1949). 53681 records from Estonian Museum of Natural History. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 15107 records from Wetland Invertebrate and Environmental Data 2010. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 11 records from Pollen profile from sediment core AV14_K2-1. 1020 records from National Museum Of Marine Science & Technology. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2202 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 17 records from Broch H. 1935. The fishery grounds near Alexandria. III Cirripeds. Notes et Memoires No 10.. 3330 records from Collection botanique Le Grand A. (BOUM). 837 records from Stable Isotope Compositions of tubeworms, mussels, and their associated fauna in Gulf of Mexico hydrocarbon seeps. 15 records from Deep-sea squat lobsters of the genus Paramunida Baba, 1988 (Crustacea: Decapoda: Munididae) from north-western Australia: new records and description of three new species. 3 records from A revision of the Eudarcia glaseri - species group (Lepidoptera, Meessiidae) with description of two new species from Greece and Crimea. 233 records from Shieldbug Records. 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1321 records from Herbier National de Mauritanie (HNM). 2775 records from Bolivian Amazon lowland fish metacommunity data. 262 records from Código de barras de ocho complejos de especies de aves mexicanas. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 5 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 238 records from List of Lichen Species recorded on high ground in the Ben Nevis range. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 17872 records from University of California Museum of Paleontology. 3 records from A new species of the spider genus Plator (Trochanteriidae) from south China. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 1 records from A new species of Oreodera Audinet-Serville, 1835 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) and new geographical records. 202161 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 86277 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 8529 records from NINA botanical collection. 7 records from Bodotria jejuensis sp. nov. (Crustacea, Cumacea, Bodotriidae), a new Korean cumacean. 1226 records from M. Andrew Johnston Collection. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 10453 records from Phytoplankton from the White Sea, Barents Sea, Norwegian Sea and Arctic Basin 1993-2003. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 1052 records from Biodiversidad de coleópteros y arañas de las Sierras de Taxco-Huautla. 419508 records from Meadow and Pasture Inventory (SJV). 370 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 374 records from Macroarthropods, Godthåbsfjorden (Nuup Kangerlua) 2013, Greenland. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 3265 records from Flora acuática vascular del estado de Morelos, México. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 2752 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1001 records from Circumpolar Seabird Monitoring Plan. 7 records from Hybothoracaphis, a new genus of Nipponaphidini (Hemiptera, Aphididae, Hormaphidinae) from China and its phylogenetic placement based on multiple genes. 1506 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 4667 records from Computarización de la colección de hongos de ECOSUR, en el estado de Chiapas. 38535 records from Mammals housed at MHNG, Geneva. 785 records from DMNS Marine Invertebrate Collection (Arctos). 84521 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 6 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 1443 records from Odonata of the Congo River 2010 expedition. 1244 records from Mosquitoes_of_French_Guiana. 8365 records from Actualización de la base de datos y la colección de hipéridos (Crustacea) y sifonóforos (Cnidaria) del Atlántico mexicano. 3 records from Three new species of entimine weevils in Early Miocene amber from the Dominican Republic (Coleoptera: Curculionidae). 3984 records from Las monocotiledóneas mexicanas, una sinopsis florística. 1301 records from Lichen diversity in grasslands. 1 records from Cladorhiza corallophila sp. nov., a new carnivorous sponge (Cladorhizidae, Demospongiae) living in close association with Lophelia pertusa and Madrepora oculata (Scleractinia). 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 75470 records from ALCB - Herbário Alexandre Leal Costa. 833 records from Reevaluación taxonómica de las especies de algas coralinas (Corallinales; Rhodophyta) que forman mantos de rodolitos en el Golfo de California, México. 56 records from Onychophora of Costa Rica (INBio). 152 records from Coleção de Platyhelminthes do Museu Nacional - UFRJ. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 102 records from Liste des plantes médicinales utilisées dans la préfecture de Labé et observées sur le terrain.. 2456 records from HUSC - Herbário Unisanta. 23215 records from rmca-albertine-rift-butterflies. 2 records from A new cave species of Coecobrya Yosii (Collembola, Entomobryidae, Entomobryinae) from South Africa, with an identification key to the genus. 14540 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 2653 records from Florida Keys Reef Visual Census 2005. 68 records from Chinches patinadoras (Hemiptera: Heteroptera: Gerridae) de Colombia: taxonomía, distribución y datos biológicos. 119584 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from A new species in the Simulium vernum group from the Alps of southern Germany: Simulium arminii (Diptera: Simuliidae). 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 104356 records from mel. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 5 records from Pamphagidae (Orthoptera: Acridoidea) from the Palaearctic Region: taxonomy, classification, keys to genera and a review of the tribe Nocarodeini I. Bolívar. 5 records from A new biogeographically disjunct giant gecko (Gehyra: Gekkonidae: Reptilia) from the East Melanesian Islands. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 34 records from Catalogue of the type specimens of Bufonidae and Megophryidae (Amphibia: Anura) from research collections of the Zoological Institute, Russian Academy of Sciences. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 1307 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 4 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 1390 records from Aves de México I. 8441 records from Natural England - Batsites inventory for England. 1 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 160023 records from Estonian University of Life Sciences. 201574 records from Essig Museum of Entomology. 23128 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 1012 records from Freshwater Shad Monitoring Data. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 13298 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 174332 records from CAS Ichthyology (ICH). 1243 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 40 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 189 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 16971 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 2 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 113 records from Distribution data of Arctic species of genus Microporella and Pseudoflustra gathered from museum collections. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 1862 records from corrego_fazendinha-gallery-forest_v2. 53606 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 15219 records from Census of the animals of Benin. 8130 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 68 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 14072 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 34 records from Order Araneae. 7078 records from Biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Oir river (France). 761 records from Dorset Heath - NBN South West Pilot Project Case Studies. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 27206 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 906 records from Netzfluegler_Raw1. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 631 records from Habitat-forming Cold Water Corals in the New Zealand region. 1189 records from kerkyra. 1116 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 22029 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 1826 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 9 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 3327 records from BioGIS - Mammals - SPNI. 13405 records from DMNS Mammal Collection (Arctos). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 17435 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 26014 records from Base de Datos de Flora de la Cuenca del Río Orinoco en Colombia. 57 records from Freshwater Gwyniad Survey Data. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 7337 records from Inventario ictiofaunístico en tres regiones hidrológicas prioritarias de la Cuenca del Grijalva-Usumacinta en el estado de Chiapas. 96 records from Dinámica poblacional de cactáceas amenazadas. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 214 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 24211 records from Monitoring data from the federal state Saxony (Germany). 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 61 records from Canada_BasinMegabenthos2002. 3 records from Two new species of Bradynobaenus Spinola, 1851 (Hymenoptera: Bradynobaenidae) in the semiarid area of Argentina. 4 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 725 records from Southern right whales distribution in Bahía Nueva, Puerto Madryn, Argentina. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 2 records from An annotated checklist of Malachiidae (Coleoptera: Cleroidea) from Iran. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 1376 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 6860 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 45971 records from TNHC Ichthyology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 13624 records from Mammal collection, Natural History Museum, University of Oslo. 10 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 1512 records from tree climbing bryophytes & lichens at tree base and crown with traits. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 128 records from Birdrace-Brut-Wetteraukreis. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 120 records from Birdrace-Kosmos_Racer-Freising. 248 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 114 records from Birdrace-Finkenspötter-München. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 746 records from Literature based species occurrence data of birds of North-East India. 112 records from Birdrace_Die_Borner-Viersen. 111 records from Birdrace-Uhulogen-Lippe. 109 record
Keywords: GBIF; biodiversity; species occurrences